Uji Efektifitas Ekstrak Daun dari Beberapa Jenis Tanaman untuk Mengendalikan Nematoda Puru Akar Meloidogyne Spp. pada Tanaman Cabai (Capsicum Annum L) - JAYA, IDA BAGUS MADE DWI; SRITAMIN, MADE; PUSPAWATI, NI MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.3, No.2, April 2014)
ABSTRACT Root knot nematodes ( Meloidogyne spp .) is an important class of nematode that causes significant reduction in the production of Capsicum annum L . Various control measures were taken to suppress the population of Meloidogyne spp . such as planting resistant varieties , crop rotation and technical culture , still unwell provide fast response compared to chemical control . Biopesticides is a way of controlling the use of more environmentally friendly than synthetic pesticides . Based on this, it will be carried out studies on the control of root knot nematodes Meloidogyne spp . using plant leaves tembelekan ( Lantana camara ), kirinyuh ( Chromolaena odorata ), papaya ( Carica papaya ), lemongrass ( Cymbopogon nardus L . ), betel ( Piper betle L . ) and tobacco ( Nicotiana tabacum ) which extracts used were 250cc / pots of each extract solution leaves. The purpose of this study was to determine the plant leaf extract is capable of suppressing the population of Meloidogyne spp . and determine the most effective leaf extracts suppress the population of Meloidogyne spp . The results of this empirically found that population of nematoda per 300 grams of soil extract of Piper betle L. can suppressed the nematode population of Meloidogyne spp. The best is 23.4 nematodes or 95.32%, followed by treatment of the extract of C. odorata 27.6 nematodes (94.48%), L. camara 28.8 nematodes (94.24%), Carica papaya 43, 4 nematodes (91.32%), Cymbopogon nardus L. 53.8 nematodes (89.4%), and Nicotiana tabacum 60.8 nematodes (87.84%). Population of nematoda per 1 g of root , extract of Piper betle Linn . is also the most well extract in suppressing root knot nematode populations , there are only recorded 21.2 percentage suppression tail with 95.76 %, followed by treatment of C. odorata extract 23.6 tail ( 95.28%), L. camara 24 , 2 goats ( 95.16%), Carica papaya 28.4 tail ( 94.32%), Cymbopogon nardus ( L) . 30.2 tail ( 93.96%), and Nicotiana tabacum 35.2 tail ( 92.96%) . Keyword: Capsicum annum L, Carica papaya , Chromolaena odorata , Cymbopogon nardus L. , Lantana camara , Meloidogyne spp., Nicotiana tabacum, Piper betle Linn.
Keywords: Capsicum annum L, Carica papaya, Chromolaena odorata, Cymbopogon nardus L., Lantana camara, Meloidogyne spp., Nicotiana tabacum, Piper betle Linn.